Voltage sags matching to locate faults for underground distribution networks - Mokhlis, Hazlie; Mohamad, H.; Li, H.Y.; Abu Bakar, A. (Advances in Electrical and Computer Engineering, 2011)
A voltage sags matching to locate a fault for underground distribution network is presented in this paper. Firstly the method identifies the faulted section by matching a voltage sags measured at the primary substation during a fault with pre-developed voltage sag database. From the identified faulted section, the distance of a fault from sending-end is calculated. The problem of multiple sections is addressed by ranking approach. Test results on an underground distribution network shows most faults can be located by the first attempt within high accuracy distance. Only few faulted sections found by the second attempt. Since the method is using only voltage sag data, monitored at the primary substation, the method is considers economical to be implemented for a rural distribution network.